Electrode voltage fall and total voltage of a transient arc. (23rd May 2016) - Valensi, F; Ratovoson, L; Razafinimanana, M; Masquère, M; Freton, P; Gleizes, A
Abstract: This paper deals with an experimental study of the components of a transient arc total voltage with duration of a few tens of ms and a current peak close to 1000 A. The cathode tip is made of graphite whereas the flat anode is made either of copper or of graphite; the electrodes gap is a few mm. The analysis of the electrical parameters is supported and validated by fast imaging and by two models: the first one is a 2D physical model of the arc allowing to calculate both the plasma temperature field and the arc voltage; the second model is able to estimate the transient heating of the graphite electrode. The main aim of the study was to detect the possible change of the cathode voltage fall (CVF) during the first instants of the arc. Indeed it is expected that during the first ms the graphite cathode is rather cool and the main mechanism of the electron emission should be the field effect emission, whereas after several tens of ms the cathode is strongly heated and thermionic emission should be predominant. We have observed some change in the apparent CVF but we have shown that this apparent change can be attributed to the variation of the solid cathode resistance. On the other hand, the possible change of CVF corresponding to the transition between a 'cold' and a 'hot' cathode should be weak and could not be characterized considering our measurement uncertainty of about 2 V . The arc column voltage (ACV) was estimated by subtracting the electrode voltage fall from the total arc voltage. The experimental transient evolution of the ACV is in very good agreement with the theoretical variation predicted by the model, showing the good ability of the model to study this kind of transient arc.